Anti-Biofilm Inhibitory Synergistic Effects of Combinations of Essential Oils and Antibiotics - Antonio Rosato; Sabina Sblano; Lara Salvagno; Alessia Carocci; Maria Lisa Clodoveo; Filomena Corbo; Giuseppe Fracchiolla (MDPI AG, 2020)
In recent years, the increase of bacteria antibiotic- resistance has been a severe problem for public health. A useful solution could be to join some phytochemicals naturally present in essential oils (EOs) to the existing antibiotics, with the aim to increase their efficacy in therapies. According to in vitro studies, EOs and their components could show such effects. Among them, we studied the activity of Cinnammonum zeylanicum, Mentha piperita, Origanum vulgare, and Thymus vulgaris EOs on bacterial biofilm and their synergism when used in association with some common antibiotics such as norfloxacin, oxacillin, and gentamicin. The chemical composition of EOs was determined using gas chromatography (GC) coupled with mass spectrometry (MS) techniques. The EOs drug efficacy was evaluated on four different strains of Gram-positive bacteria forming biofilms. The synergistic effects were tested through the chequerboard microdilution method. The association EOs-antibiotics showed a strong destruction of the biofilm growth of the four bacterial species considered. The interaction of norfloxacin with EOs was the most effective in all the tested combinations against the strains object of this study. These preliminary results suggest the formulation of a new generation of antimicrobial agents based on a combination of antimicrobial compounds with different origin.